THE USE OF MODERN TECHNOLOGIES IN TEACHING UZBEK LANGUAGE TO FOREIGNERS - Usmonova Zamira Jaxongirovna (Web of Journals Publishing, 2025)
The Uzbek language, with its rich culture and historical heritage, is considered interesting and useful for learning for foreigners. Today, due to the processes of globalization and the development of information technologies, the opportunities for foreigners to use modern technologies for teaching the Uzbek language expand. In this article we will consider the importance of modern technologies in the teaching of Uzbek language to foreigners, their advantages and their application.
Keywords: Uzbek language, modern technologies, online platforms, resources, interactive programs, information technologies.